2023
DOI: 10.3389/fnhum.2023.1077234
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of dysphagia in stroke: A systematic review and meta-analysis

Abstract: ObjectivesDysphagia is a major cause of stroke infection and death, and identification of structural and functional brain area changes associated with post-stroke dysphagia (PSD) can help in early screening and clinical intervention. Studies on PSD have reported numerous structural lesions and functional abnormalities in brain regions, and a systematic review is lacking. We aimed to integrate several neuroimaging studies to summarize the empirical evidence of neurological changes leading to PSD.MethodsWe condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Such diseases include stroke, Parkinson’s disease, and multiple sclerosis, among other neurodegenerative disease processes ( Chandran and Doucet, 2024 ). Dysphagia following stroke primarily stems from cerebral cortex and subcortical structures damage, affecting areas like the motor cortex, cerebellum, thalamus, and other parts, as well as sensory defects of the pharyngeal mucosa ( Teismann et al, 2007 ; Qin et al, 2023 ). It is characterized by a delayed or absent swallowing reflex and a premature overflow of bolus ( Labeit et al, 2023 ), pharyngeal food residues and pharyngeal motility disorders ( Warnecke et al, 2021 ).…”
Section: Mechanisms Associated With Dysphagiamentioning
confidence: 99%
“…Such diseases include stroke, Parkinson’s disease, and multiple sclerosis, among other neurodegenerative disease processes ( Chandran and Doucet, 2024 ). Dysphagia following stroke primarily stems from cerebral cortex and subcortical structures damage, affecting areas like the motor cortex, cerebellum, thalamus, and other parts, as well as sensory defects of the pharyngeal mucosa ( Teismann et al, 2007 ; Qin et al, 2023 ). It is characterized by a delayed or absent swallowing reflex and a premature overflow of bolus ( Labeit et al, 2023 ), pharyngeal food residues and pharyngeal motility disorders ( Warnecke et al, 2021 ).…”
Section: Mechanisms Associated With Dysphagiamentioning
confidence: 99%
“…Voxel-Based Morphometry (VBM) [48,49] is a neuroimaging technique used to detect and analyze structural changes in the brain, making it a valuable tool for identifying pathological brains. VBM involves comparing an individual's brain image to a standardized brain template or atlas.…”
Section: Voxel-based Morphometrymentioning
confidence: 99%
“…6 Tongue Push Forward Open mouth and move tongue such that tongue tip rests against the lower lip, patient attempts to move tongue forward, hold for 5 seconds, repeat 10 times. 7 Tongue Push Up Extend tongue out of mouth, patient attempts to move tongue upward against the upper lip, hold for 5 seconds, repeat 10 times…”
Section: Sno Exercises Instructionsmentioning
confidence: 99%
“…Some patients with severe dysphagia requires a nasogastric feeding tube for months, even to years to compensate for adequate nutrition demand and water intake [6]. The structural neuroimaging analysis in poststroke dysphagia patients found that the insular cortex, frontal lobe, temporal gyrus, basal ganglia, postcentral gyrus, precentral gyrus, precuneus, and radial corona were the relevant brain areas for dysphagia and the insular cortex probably had the greatest association with poststroke dysphagia [7].…”
Section: Introductionmentioning
confidence: 99%